Heparanase Facilitates PMA-Induced Megakaryocytic Differentiation in K562 Cells via Interleukin 6/STAT3 Pathway - Wan, Lu Ming; Zhang, Shi Kun; Li, Su Bo; Li, Wen; Ji, Shou Ping; Gong, Lin; Yun, Zhi Min; Zhang, Xue; Gao, Hong Wei; Zhong, Hui; Wei, Cong Wen; Bian, Li Hong; Zhuo, Hai Long; Luo, Qun; Li, Jin Ping; Tan, Ying Xia; Gong, Feng (Thrombosis and Haemostasis, 2020)
Heparanase (HPSE) is an endo-β-D-glucuronidase that cleaves heparan sulfate and hence participates in remodeling of the extracellular matrix, leading to release of cytokines that are immobilized by binding to heparan sulfate proteoglycans (HSPGs), and consequently activating signaling pathways. This function of HPSE is correlated to its expression level that is normally very low in majority of the tissues. Exceptionally, human platelets express high level of HPSE, suggesting a unique physiological role in this cell. Using K562 cell line, we found a progressive increase of HPSE during the megakaryocytic differentiation. Analysis of a series of megakaryocytic differentiation-related heparin-binding proteins (HBPs) in the cell culture medium revealed an exclusive positive correlation between the level of interleukin 6 (IL-6) and HPSE expression. IL-6 modulated megakaryocytic differentiation through activation of STAT3. Further, we demonstrated that overexpression of HPSE potentiates megakaryocytic differentiation, whereas elimination of HPSE led to a delayed differentiation. This function of HPSE is associated with its activity, as overexpression of inactive HPSE had no effect on IL-6 production and megakaryocytic differentiation. The role of HPSE is further supported by the observation in an umbilical cord blood CD34+ cells megakaryocytic differentiation model. Our data propose a novel role for HPSE in platelets production by a HPSE/IL-6/STAT3 positive feedback loop that specifically regulates megakaryocytes maturation.
Keywords: heparanase; megakaryocytic differentiation; interleukin 6; STAT3